Assessing Democracy Assistance : The Case of Romania - Carothers, Thomas, 1956- (Book collections on Project MUSE., 1996)
In recent years, assistance aimed at promoting democracy abroad has become a major component of U.S. foreign aid and of the U.S. government's post-Cold War policy of seeking to enlarge the international community of democratic nations. Despite its rapid growth, however, democracy assistance remains poorly understood in practice, and its value is frequently questioned. This landmark study, an examination of U.S. democracy assistance efforts in Romania, is the first comprehensive analysis of the workings - and failings - of U.S. democracy assistance in one country. Based on the author's extensive field research, the study provides widely applicable answers to key questions about the value, strategies, methods, and future of such assistance.